Bahasa: Antara Pikiran dan Tindakan - Rahardjo, Mudjia (ULUL ALBAB Jurnal Studi Islam, 2001)
Language, idea and action are closely related. It starts from cultivating an idea expressed in a language which creates an action. In certain extent, however, language does not perfectly picture what we think, feel and understand As a result, what we express in language is not necessarily the same as what we expect. This might create misunderstandings. From this point of view, language doesn't merely consist of words constructed in certain patterns suitable with certain grammatical rules, but language should also deliver the intended message.